Determinants of Mobile Banking Adoption Among Customers of Agricultural Development Bank - Kyei Kwabena; Oscar Agyemang Opoku (Garuda Prestasi Nusantara Consulting, 2023)
The study sought to analyse the determinants of mobile banking adoption among bank customers of Agricultural Development Bank. Explanatory design of quantitative approach was used. A simple random sampling technique was used to select 420 respondents of which 380 successfully responded yielding a 90% response rate. Questionnaire was the main data collection instrument used and the data collected are analyzed using Structural Equation Modeling. The study found that communication, pursuance, perceived risk, perceived usefulness and transaction speed as the significant determinants of mobile banking adoption. In addition, respondents identify poor internet connectivity and high service charges as the main challenges associated with mobile banking. Therefore, it is recommended that Agricultural Development Bank should ensure speed and cost efficiency in its mobile banking service. Furthermore, mobile banking departments activities need to be closely supervised and audited in evaluating the developments, expansions and challenges of services rendering.